Socialization of the Sustainable Construction Management Budget through Community Service in the Mekarsari Boarding House Construction Project - Mustofa, Imam; Azhari, Faiz Muhammad; Rahmahima, Bella Amiria (Universitas Negeri Padang, 2024)
Sustainable construction management has become an important issue in this modern era due to limited natural resources, climate change and environmental problems. One construction sector that has great potential for implementing sustainable development principles is boarding houses. The demand for affordable and comfortable boarding houses continues to increase along with population growth and urbanization. However, unsustainable boarding house construction can have a negative impact on the environment and public health. Socialization of the sustainable construction management budget for the Mekarsari boarding house construction project through community service aims to introduce sustainable practices to relevant stakeholders. In the implementation method, identifying weaknesses, training, community formation, evaluation, and knowledge dissemination are key steps. The results of this community service include increasing the knowledge of project partners, forming a community that cares about sustainable development, and implementing sustainable practices in boarding house construction projects. Even though there are challenges, such as paradigm changes and regulatory complexity, this community service has great potential to become an inspiring example in the construction industry. The importance of continuing support for sustainable practices, increasing knowledge dissemination, realizing regulations, integrating technological innovation, and promoting cross-sector collaboration. By following these suggestions, this project can have a greater impact in driving positive change in the construction industry towards more sustainable development.